Stability of multistate configurations of fuzzy dark matter. Issue 1 (1st February 2021) - Guzmán, Francisco S.
Abstract: We study the stability properties of multistate configurations of the Schrödinger‐Poisson system without self‐interaction, with monopolar and first dipolar components (1, 0, 0) + (2, 1, 0). We show that these studied configurations are stable using numerical simulations and using criteria of stationarity, unitarity, and time dependence consistency. The study covers a range of states with a monopolar to dipolar mass ratio of between 47 and 0.17. The astrophysical implication of this result is that this type of configurations is at least stable and can be considered physically sound in multistate ultralight bosonic dark matter.